2013
DOI: 10.1523/jneurosci.1483-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Mediated Plateau Potentials in Lumbar Motoneurons of Neonatal Rats

Abstract: The development and the ionic nature of bistable behavior in lumbar motoneurons were investigated in rats. One week after birth, almost all (ϳ80%) ankle extensor motoneurons recorded in whole-cell configuration displayed self-sustained spiking in response to a brief depolarization that emerged when the temperature was raised Ͼ30°C. The effect of L-type Ca 2ϩ channel blockers on self-sustained spiking was variable, whereas blockade of the persistent sodium current (I NaP ) abolished them. When hyperpolarized, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 122 publications
5
61
0
3
Order By: Relevance
“…Moreover, the presence of sustained depolarization with repetitive spikes on motoneurons was not necessarily related to the functional significance of recorded motoneurons, since both mainly flexor (L1–L2; Kiehn & Kjaerulff, ) and mainly extensor (L4–L5; Kiehn & Kjaerulff, ) motoneurons showed this behavior. Proportions of motoneurons with or without sustained depolarization in this study are comparable to those reported in other studies (Perrier & Hounsgaard, ; Bouhadfane et al, ). Yet, it remains to be determined if there are differences in how histamine modulates motoneuron output and spinal activity in the developing versus the mature spinal cord.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the presence of sustained depolarization with repetitive spikes on motoneurons was not necessarily related to the functional significance of recorded motoneurons, since both mainly flexor (L1–L2; Kiehn & Kjaerulff, ) and mainly extensor (L4–L5; Kiehn & Kjaerulff, ) motoneurons showed this behavior. Proportions of motoneurons with or without sustained depolarization in this study are comparable to those reported in other studies (Perrier & Hounsgaard, ; Bouhadfane et al, ). Yet, it remains to be determined if there are differences in how histamine modulates motoneuron output and spinal activity in the developing versus the mature spinal cord.…”
Section: Discussionsupporting
confidence: 91%
“…I NaP also contributes to the induced oscillations in some rodent spinal interneurons (Bouhadfane et al 2013; Tazerart et al 2008; Ziskind-Conhaim et al 2008). I NaP may help to stabilize the fictive locomotion rhythms in neonatal rats (Tazerart et al 2007) and is suggested to have an essential role in the generation of neonatal mouse locomotion pattern (Zhong et al 2007) or in generating the rat masticatory movements (Brocard et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…En fait, son rôle est bien plus complexe. Le motoneurone possède la propriété de décharge non-linéaire nommée « potentiel de plateau » [22]. Cette propriété, intrinsèque au motoneurone, se manifeste par l'émission continue de potentiels d'action à la suite d'une brève dépolarisation (Figure 3a et 3b).…”
Section: Qu'est-ce Que La Spasticité ?unclassified
“…Cette propriété, intrinsèque au motoneurone, se manifeste par l'émission continue de potentiels d'action à la suite d'une brève dépolarisation (Figure 3a et 3b). Nous avions démontré antérieurement que le courant sodique persistant (I NaP ), largement exprimé au sein du réseau locomoteur [23][24][25][26], est essentiel dans cette décharge en plateau [22]. Ce courant augmente considérablement à la suite d'une lésion de la moelle épinière (Figure 3c) et contribue à l'hyperexcitabilité motoneuronale en favorisant l'émer-gence des potentiels de plateau de très longue durée [27] (Figure 3d).…”
Section: Qu'est-ce Que La Spasticité ?unclassified
See 1 more Smart Citation